Dl-3-n-Butylphthalide Exerts Dopaminergic Neuroprotection Through Inhibition of Neuroinflammation - Chen, Yajing; Wu, Tingting; Li, Heng; Li, Xuan; Li, Qing; Zhu, Xiaoying; Yu, Mei; Kuo, Sheng-Han; Huang, Fang; Wu, Yun-Cheng (Frontiers in Aging Neuroscience, 2019)
Microglia-mediated neuroinflammation contributes to multiple neurodegenerative disorders, including Parkinson’s disease (PD). Therefore, the regulation of microglial activation probably has the therapeutic potential. This study is aimed to determine whether dl-3-n-butylphthalide (NBP) could suppress microglial activation and protect dopaminergic neurons from excessive neuroinflammation. In the present study, 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD model was established to explore the neuroprotective and anti-inflammatory effect of NBP. We assessed motor deficits, dopaminergic neurodegeneration and microglial activation in PD mice. In vitro, the anti-inflammatory activity of NBP was confirmed by cell viability assay of SH-SY5Y cells after being treated with conditioned medium from lipopolysaccharide (LPS)-stimulated BV-2 cells and from 1-Methyl-4-phenylpyridinium iodide (MPP+)-stimulated BV-2 cells. The expression of pro-inflammatory molecules was determined by RT-PCR, Western Blot and Elisa assay. The generation of nitric oxide (NO) and reactive oxygen species (ROS) were also assessed. The involvement of signaling pathways such as mitogen-activated protein kinase (MAPK), nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB), and PI3k/Akt were further investigated by Western Blot and immunofluorescence assay. The neuroprotective effect of NBP was demonstrated in vivo as shown by the improvement of dopaminergic neurodegeneration, motor deficits and microglial activation in MPTP-induced mouse model of PD. The expression of pro-inflammatory mediators was also reduced by NBP administration. In vitro, NBP also protected dopaminergic neurons from neurotoxicity induced by activated microglia. NBP pretreatment not only reduced pro-inflammatory molecules, but also suppressed NO release and ROS generation in BV-2 cells. Further mechanism research suggested that the inactivation of MAPK, NF-κB and PI3K/Akt may involve in anti-neuroinflammation role of NBP. In conclusion, our results revealed that NBP exerted dopaminergic neuroprotection through inhibition of microglia-mediated neuroinflammation, suggesting the promising therapeutic effect of NBP for PD.